2019
DOI: 10.1111/bld.12262
|View full text |Cite
|
Sign up to set email alerts
|

The impact of books on social inclusion and development and well‐being among children and young people with severe and profound learning disabilities: Recognising the unrecognised cohort

Abstract: Br J Learn Disabil. 2019;47:91-104. wileyonlinelibrary.com/journal/bld | 91 Accessible Summary• This paper shows what people with learning disabilities can get out of enjoying books and reading even when they cannot read words easily.• The writers think about how people with learning disabilities can be helped to enjoy books. They say that this can happen through reading with other people, enjoying lots of activities about books and making books part of their daily routine.• The writers also think about the wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Espinosa-Montero et al 2016developed an instrument to measure the relationship between water consumption and well-being using empirical data from a lowincome adult population in an urban area, which can be useful in other contexts. Finally, Robinson et al (2019) found a positive impact of engaging with books on the well-being of children and young adults with severe and profound learning disabilities, which is in line with what the Children and Families Act of 2014 required in England. What all these examples have in common is the fact that they are oriented to responding to societal needs, sometimes by including stakeholders' knowledge about their daily life experience.…”
Section: Conceptual Framework Of the Social Impact In Well-being Resesupporting
confidence: 75%
“…Espinosa-Montero et al 2016developed an instrument to measure the relationship between water consumption and well-being using empirical data from a lowincome adult population in an urban area, which can be useful in other contexts. Finally, Robinson et al (2019) found a positive impact of engaging with books on the well-being of children and young adults with severe and profound learning disabilities, which is in line with what the Children and Families Act of 2014 required in England. What all these examples have in common is the fact that they are oriented to responding to societal needs, sometimes by including stakeholders' knowledge about their daily life experience.…”
Section: Conceptual Framework Of the Social Impact In Well-being Resesupporting
confidence: 75%
“…Eve's mother Anna noted that children with PMLD were more typically directed to sensory ‘cause and effect’ apps—for example, where placing your hand on the touchscreen is rewarded with a visual burst of fireworks or a sound effect—and subsequently had not considered the possibility of storymaking apps like Pictello. By repositioning children with the most severe disabilities as co‐authors through the lens of distributed authorship, engagement with storymaking is legitimated as a worthwhile and meaningful activity, which in turn contributes to wider goals of ‘inclusive literacy’ (Robinson et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Rather one of these papers discussed how we experience the world through our senses (Aspán et al, 2020) and the other referred to sensoriality and sensory perception (Pacheco-Costa & Guzmán-Simón, 2021). AND "child*" OR "toddler*" OR "student" OR "pupil" OR "infancy" OR "preschool*" OR "pre-school*" OR "pre-k" OR "kindergarten*" OR "kindergartner*" OR "ECEC" OR "ECE" OR "daycare*" OR "day-care*" OR "day care*" OR "primary school*" OR "junior school*" OR "elementary school*" OR "grade school*" OR "grammar school*" OR "graded school*" OR "junior school*" OR "preparatory school*" Of the four papers that discussed both multisensory and embodiment, one study (Glenberg et al, 2011) referred to two individual senses, whilst three papers (Labat et al, 2020, Zhou, 2021and Robinson et al, 2019 referenced four or five individual senses.…”
Section: Theoretical Characteristics Of the Reviewed Studiesmentioning
confidence: 99%